Benthic biodiversity off the eastern mouth of the Strait of Magellan (Argentina, south-west Atlantic) - Centurion, Romina Luisa Sabrina (2012)
The analysis of changes in benthic community structure using multivariate techniques has been successfully applied to the detection and monitoring of impacts caused by oil related activities. A survey to assess the status of the benthos was performed prior to a scheduled exploratory drilling at Banco Sarmiento, a shoal located off the eastern mouth of the Strait of Magellan (south-west Atlantic). The aims of this study are to provide baseline data about the composition and structure of the subtidal macrobenthic assemblages, to analyse the relationships between biodiversity and environmental variables, and to compare its benthic assemblages with those of neighbouring areas. Multivariate analyses classified the stations in two major groups, one composed of relatively shallow stations with coarse sediments dominated by filter-feeders, and the other consisting of stations with a high proportion of sand and mud dominated by deposit-feeders. Poorly sorted sediments had higher species richness than well sorted sediments. Shallow stations showed the lowest taxonomic distinctness due to the occurrence of a high proportion of bryozoans encrusting hard substrata. A five-fold increase in biodiversity can occur at scales of tens of km, suggesting that generalizations on regional biodiversity patterns should be made with caution because of the different gears used during the collection of samples, and should be based on a thorough knowledge about the physical environment.